Analysis of the Effectiveness of Shielded Band Spraying in Weed Control in Field Crops - Osuch, Andrzej; Przygodziński, Przemysław; Rybacki, Piotr; Osuch, Ewa; Kowalik, Ireneusz; Piechnik, Leszek; Przygodziński, Arkadiusz; Herkowiak, Marcin (Agronomy (Basel), 2020)
An important factor along with the availability of food is its quality. It depends, among other things, on the type of plant protection products used and the method of their application. This manuscript presents research on the possibility of using a shielded band sprayer in field onion cultivation. The shielded band spraying technology presented in this article is the subject of a patent application (application number P.428494-The prototype of the machine was produced in Poland in cooperation with the University of Life Sciences in Poznań). The research consisted in comparing the quantity and quality of the obtained crop, based on various methods of reducing the weed population. The research results indicate that the proposed shielded band spraying technology may affect the food quality (the active substance is not sprayed on onion plants) and profitability of farms (less use of plant protection products).